Professional responsibility between guidelines and customary practice. A conflict of interest?. (January 2022) - Tebala, Giovanni D.; Slack, Zoe; Fantini, Vittoria; Masato, Sarah; Parla, Massimiliano; Cirocchi, Roberto; Di Saverio, Salomone
Abstract: In Countries with Common Law, the principles of medical liability in case of malpractice claim are based on the Bolam/Bolitho tests, that is, the opinion of a panel of average professionals of the same specialty. On the contrary, in Countries whose legal system is based on the Corpus Iustinianeum the practice of a doctor is benchmarked against established guidelines. Occasionally, the opinion of an expert panel may not overlap the formal guidelines, in particular in cases like the surgical treatment of acute diverticulitis and that of acute cholecystitis where pre-existing old-fashioned ideas are so rooted into the behaviour of doctors that they are extremely difficult to eradicate despite the growing amount of evidence. This may lead to the paradox that a doctor who followed the guidelines might be considered imprudent or negligent as his or her choice did not overlap that of the "average" professional. This is a grey area that needs clarification. We propose that the "expert panel" nominated during a medical malpractice claim should not report their personal – although shared – opinion, but should unbiasedly report all the available acceptable options. Criminal and civil courts, along with other medical panels, must consider this bias when scrutinizing the practice of a professional.